OS2.3 Relevance of Neurofibromatosistype 1 and schwannomotosis in extramedullary spine tumors. (6th September 2019) - Eoli, M E; Bianchessi, D; Moscatelli, M; Chiapparini, L; Ibba, C; Finocchiaro, G; Bruzzone, M
Abstract: BACKGROUND: Extramedullary spine tumors represent two-thirds of all primary spine neoplasms. Approximately half of these are peripheral nerve sheath tumors, mainly neurofibromas and schwannomas and neurofibromatosis or schwannomatosis can be suspected. Given the rarity of this condition the clinical genetic and radiological features remains to be better define. The aim of this study was to characterize the clinical, radiologic presentation of patients with widespread spinal disease and to identify gene mutation. MATERIAL AND METHODS: We selected patient with a at least: intradural extramedullary, or extradural intraspinal (tumor within the spinal canal), or extradural paraspinal (tumor at the neural foramenor extending outward into adjacent tissues) neoplasms and no other tumors such as meningiomas in the spine at spine MRI. Patients' DNA were analyzed by Targeted NGS by means a custom gene panel including NF1, NF2, LZTR1, SMARCB1 genes. RESULTS: 63 patients were identified31 had few isolated tumors, involving spinal roots (Multiple Neurofibromas Few Spinal Root, MNFSR), 18 had bilateral neurofibromas involving all spinal roots. 14 had a single lesion; 10 cases were familiar and 53 sporadic. Genetic analysis showed NF1 gene mutations (in prevalence splicing or missense) in 49 cases LZTR1 mutations in 3 and in the others 11 no mutation or deletion was detected. Pain was the hallmark symptom in patients with LZTR1 mutations, while all familial cases all had NF1 diagnosis. About 50% of them had few cutaneous manifestations. CONCLUSION: In patients with extramedullary spine tumors is important to look for signs of neurofibromatosis or schawannomatosis and if there are present genetic testing should be performed.